Controlling Neutral Plane of Flexible Substrates by Asymmetric Impregnation of Glass Fabric for Protecting Brittle Films on Foldable Electronics. Issue 6 (14th March 2021) - Jo, Woosung; Lee, Hyunhwan; Lee, Yung; Bae, Byeong-Soo; Kim, Taek-Soo
Abstract : Neutral plane strategies have been studied to reduce the tensile strain of brittle films in foldable electronics under bending. However, those strategies depend on the dimensions of components in devices, implying that they could be limited to application to various designs of devices. Herein, the glass fabric's position in a glass fabric–reinforced siloxane hybrid substrate is shifted to control the neutral plane of the substrate. Due to the stiffness difference between the glass fabric and epoxy siloxane hybrid matrix, the neutral plane of the substrate is affected by the position of the glass fabric. Therefore, the glass fabric is asymmetrically impregnated to be located at the substrate surface so as to shift the neutral plane of the substrate toward the surface. The effectiveness of the newly developed substrate is proved by comparison with a conventional colorless polyimide substrate. The neutral plane position and maximum tensile strain of the substrates are investigated by analytical calculation, digital image correlation analysis, bending test, and finite element method simulation. The results clearly show that the newly developed substrate–based structure can reduce the maximum tensile strain under bending. Consequently, the cracking of the brittle hard coating is effectively prevented. Abstract : A flexible substrate with a controlled neutral plane is proposed in this study. The newly suggested substrate can reduce the maximum tensile strain of the substrate under bending. The developed substrate can prevent the cracking of the brittle hard coating on the thick substrate and laminate structure, implying that it can contribute to commercializing robust foldable electronics.